Spleen volume in relation to ulcerative colitis and Crohn’s disease: a Mendelian randomization study - Qiang Su; Jian Li; Yun Lu; Jiang Liang; Song Huang; Min Wu; Yuanli He; Zhenxiang An; Jinbing Ding; Zhizhong Zhang (Scientific Reports)
Abstract Prior research has established the significance of spleen volume (SV) in the pathogenesis and advancement of ulcerative colitis (UC) and Crohn’s disease (CD). Nevertheless, these investigations are predominantly observational, thereby leaving their causal associations ambiguous. Moreover, the breadth of existing research is constrained by various uncontrollable variables in clinical settings. This study aims to deduce the causal link between SV and the susceptibility to UC and CD through a genetic perspective. The objective of this study was to investigate the genetic association between SV and inflammatory bowel disease (IBD) risk using Mendelian randomization (MR) analysis. Single nucleotide polymorphisms (SNPs) associated with SV were used as instrumental variables. Genetic associations for UC and CD were extracted from the International Inflammatory Bowel Disease Genetics Consortium (IIBDGC), the FinnGen study, and other publicly available genome-wide association studies (GWAS). Methods such as inverse variance weighted, Bayesian weighted Mendelian randomization (BWMR), contamination mixture (ConMix), along with sensitivity analyses and the Steiger test were used in the study. A meta-analysis was conducted to synthesize the results. The study found that genetically predicted SV was associated with an increased risk of UC in the IIBDGC dataset (OR = 1. 223, 95% CI: 1. 055–1. 417, P = 0. 008), FinnGen (OR = 1. 169, 95% CI: 1. 003–1. 363, P = 0. 045), the GWAS study by Sakaue S (OR = 1. 188, 95% CI: 1. 008–1. 399, P = 0. 040), and in the meta-analysis (OR = 1. 115, 95% CI: 1. 014–1. 227, P = 0. 025). Similarly, genetically predicted SV was associated with an increased risk of CD in the IIBDGC dataset (OR = 1. 235, 95% CI: 1. 026–1. 488, P = 0. 026), FinnGen (OR = 1. 308, 95% CI: 1. 026–1. 667, P = 0. 030), the GWAS study by Zorina-Lichtenwalter K (OR = 1. 316, 95% CI: 1. 037–1. 670, P = 0. 024), and in the meta-analysis (OR = 1. 272, 95% CI: 1. 133–1. 428, P < 0. 001). According to the meta-analysis results, for each standard unit increase in SV, the risk of developing UC increases by 11. 5%, and the risk of developing CD increases by 27. 2%. This study presents findings that suggest a positive causal association between SV and the onset of IBD.